The Beveridge curve and labour market flows - a reinterpretation - Nils Gottfries; Karolina Stadin (Center for Economic Studies and ifo Institute (CESifo), 2019)
According to search-matching theory, the Beveridge curve slopes downward because vacancies are filled more quickly when unemployment is high. Using monthly panel data for local labour markets in Sweden we find no (or only weak) evidence that high unemployment makes it easier to fill vacancies. Instead, there are few vacancies when unemployment is high because there is a low inflow of new vacancies. We construct a simple model with on-the-job search and show that it is broadly consistent with the cyclical behaviour of stocks and flows in the labour market also without search frictions. In periods of high unemployment, fewer employed job seekers find new jobs and this leads to a smaller inflow of new vacancies.
Keywords: E24; J23; J62; J63; J64; 330; Beveridge curve; frictional unemployment; matching function; turnover; mismatch; vacancy chain